Analisis Komposit Serat Daun Pandan Alas Dan Serbuk Kayu Jati Dengan Resin Polyester Terhadap Kekuatan Tarik Dan Daya Serap Air: Analisis Komposit Serat Daun Pandan Alas - Suryono Adi Waluyo; Wahidin Nuriana; Mustafa (LPPM Universitas Merdeka Madiun, 2022)
Abstract— Pandanus fiber and teak sawdust were waste products that were abundant in availability, but have not been used optimally. Base pandanus fiber and teak sawdust were used as alternative reinforcement for composite materials. The purpose of this study was to test the tensile strength and water absorption of composites reinforced with base pandan fiber and teak sawdust with polyester resin as a matrix. This composite was made by hand lay up technique with variations in the volume fraction of coconut fiber fibers of 10%, 20%, 30%, 30%, 20%, 10% teak sawdust, 60% polyester resin with random fiber orientation, 30 mm fiber length. Composite specimens were cut according to ASTM D 638-01 standards for tensile testing and ASTM D 570 for water absorption tests. The results of this study were tensile strength, strain, modulus of elasticity with optimum strength respectively 30.28 MPa (volume fraction 30%; 10%; 60%), 1.508 mm / mm (volume fraction 10%; 30%; 60%) , 447.46 Mpa (volume fraction 10%; 30%; 60%). Water absorption was 2.07% (volume fraction 10%; 30; 60%).